2004
DOI: 10.1097/00000542-200403000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amino Acid Infusion on Central Thermoregulatory Control in Humans

Abstract: Background-Administration of protein or amino acids enhances thermogenesis, presumably by stimulating oxidative metabolism. However, hyperthermia results even when thermoregulatory responses are intact, suggesting that amino acids also alter central thermoregulatory control. We thus tested the hypothesis that amino acid infusion increases the thermoregulatory setpoint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 35 publications
2
19
0
3
Order By: Relevance
“…Most probably there is a combination of thermoregulatory and molecular factors. Proteins and amino acids may have a pyrogen-like influence and reset the set point in the awake state (16,17), possibly via a second messenger. Body oxidative metabolism keeps the body core temperature constant and prevents hypothermia in the awake state (18).…”
Section: Discussionmentioning
confidence: 99%
“…Most probably there is a combination of thermoregulatory and molecular factors. Proteins and amino acids may have a pyrogen-like influence and reset the set point in the awake state (16,17), possibly via a second messenger. Body oxidative metabolism keeps the body core temperature constant and prevents hypothermia in the awake state (18).…”
Section: Discussionmentioning
confidence: 99%
“…An explanation might be that any enhanced thermogenesis which increases oxidative metabolism leads to a concomitantly increased production of oxygen radicals and thus affects both redox and temperature homeostasis. The observation that in humans an amino acid infusion which increases metabolic rate causes a rise of the thermoregulatory setpoint supports this concept (Nakajima et al 2004).…”
Section: Fevermentioning
confidence: 94%
“…AAs is likely to enhance the quality of patient care and improve cost-effectiveness [4][5][6]. AA infusion appears to be a useful new thermoregulatory strategy for preventing hypothermia during surgery.…”
mentioning
confidence: 99%
“…According to recent reports, AAs induce an increase in energy expenditure that may be explained by several mechanisms, including an increase in the energy cost of glucose storage [7], increased anabolism [8,9], an infl uence on central thermoregulatory mechanisms [5], and hormonal regulation of mitochondrial energy production [10]. It has been reported that AA infusion stimulates the release of metabolic hormones such as insulin, cortisol, and glucagon [9], suggesting that hormonal regulation may play a part in energy expenditure.…”
mentioning
confidence: 99%